Enhancing the quantification of tissue sodium content by MRI: time-efficient sodium B1 mapping at clinical field strengths - Lommen, Jonathan Manuel; Schad, Lothar R. (NMR in biomedicine, 2016)
Tissue sodium content (TSC) is a sensitive measure of pathological changes and can be detected non-invasively by MRI. For the absolute quantification of TSC, B1 inhomogeneities must be corrected, which is not well established beyond research applications. An in-depth analysis of B1 mapping methods which are suitable for application in TSC quantification is presented. On the basis of these results, a method for simultaneous B1 mapping and imaging is proposed in order to enhance accuracy and to reduce measurement time at clinical field strengths. The B1 mapping techniques used were phase-sensitive (PS), Bloch-Siegert shift (BSS), double-angle (DAM) and actual flip?angle imaging (AFI) methods. Experimental and theoretical comparisons demonstrated that the PS technique yields the most accurate field profiles and exhibits the highest signal-to-noise ratio (SNR). Simultaneous B1 mapping and imaging was performed for the PS method, employing both degrees of freedom of the MR signal: the B1 field is encoded into signal phase and the amplitude provides the concentration information. In comparison with the more established DAM, a 13% higher SNR was obtained and field effects could be corrected more accurately without the need for additional measurement time. The protocol developed was applied to measure TSC in the healthy human head at an isotropic resolution of 4 mm. TSC was determined to be 35 ± 1 mM in white matter and 134 ± 3 mM in vitreous humor. By employing the proposed simultaneous characterization of the B1 field and acquisition of the spin density-weighted sodium signal, the accuracy of the non-invasive measurement of TSC is enhanced and the measurement time is reduced. This should allow 23Na MRI to be better incorporated into clinical studies and routine.
Gesehen am 04.02.2019
Published online in Wiley Online Library: 21 April 2015